Violence and Aggressive Behavior: Why, and How to Deal With It - Suharnan (Faculty of Psychology, Universitas Surabaya, 2010)
The purpose of this article is to understand an issue of violence and aggressive behaviors, especially in collective forms in the last decade. To determine the causes of the violence, the author proposes some psychological theories of human behavior and violence . There are frustration theory, social learning, lost of control, social identity, and lost of self-esteem. From theoretical stand point, some important strategies can be applied to solve the behavioral problems, at least reducing them. Among of the strategies are supporting new organizations such as media for actualizing and sharing, facilitating individuals to access in organizations, controlling mass media especially television in covering news of violent behaviors, developing a diversity management in various organizations, reducing critics in sarcastic and humiliating forms, and the last one is developing role of parents in educating their children and adolescents Artikel ini bermaksud ingin memahami tindak kekerasan dan agresivitas terutama di dalam bentuk kolektif yang terjadi selama dekade terakhir. Untuk menjelaskan kemungkinan penyebab terjadi kekerasan itu penulis mengajukan teori tentang perilaku manusia dan teori- teori khusus kekerasan. Sejumlah teori tentang kekerasan tersebut adalah teori frustrasi, teori kehilangan kontrol terhadap lingkungan, teori belajar sosial, teori identitas sosial, teori kehilangan harga diri. Mengacu pada pandangan teori-teori tersebut, beberapa strategi penting dapat diterapkan untuk mengatasi masalah perilaku tersebut, paling sedikit dapat mengurangi. Strategi dimaksud antara lain adalah: mendukung pembentukan organisasi- organisasi baru sebagai sarana aktualisasi diri dan ambil bagian, mempermudah individu- individu untuk mengakses ke dalam organisasi, mengendalikan media massa terutama televisi dalam meliput berita tentang berbagai tindak kekerasan, mengembangkan manajemen diversitas dalam berbagai organisasi, mengurangi kritik dalam bentuk kata-kata kasar dan penghinaan, dan terakhir adalah meningkatkan peran orang tua di dalam mendidik anak-anak dan remaja.